Numerical and optical soot characterization through 2-color pyrometry technique for an innovative diesel piston bowl design. (1st February 2023) - Piano, A.; Roggio, S.; Millo, F.; García, A.; Micó, C.; Lewiski, F.; Pesce, F.C.; Vassallo, A.; Bianco, A.
Highlights: Detailed analysis of soot reduction potential from an innovative diesel piston bowl. 2-Color pyrometry technique adopted to obtain the optical soot density KL. Two methodologies to compare the numerical soot distribution with optical KL. Good agreement between the numerical distributions and the optical soot density KL. Remarkable soot reduction enabled by the innovative bowl design. Abstract: The development of innovative diesel piston bowl designs has shown significant improvement of the near-wall flame evolution, resulting in lower fuel consumption and engine-out soot emissions. With this aim, a novel hybrid piston bowl for a 1.6 L light-duty diesel engine was designed, coupling a sharp-stepped bowl and radial-bumps in the inner bowl rim. The effects of the proposed hybrid bowl were analysed through both single-cylinder optical engine and 3D-CFD models, which feature a detailed chemical kinetic mechanism and the Particulate Mimic (PM) soot model. The 2-color pyrometry optical technique was adopted to obtain the optical soot density (KL) and the temperature of the soot surface. Then, a line-of-sight integration of the numerical soot distribution was adopted to obtain a planar KL distribution, which is directly comparable with the experimental KL images. The results showed a good agreement in terms of soot distribution between 3D-CFD and experiments, confirming the high prediction capabilities of the developed numerical methodology. The synergetic application of numerical and optical techniques highlighted that the hybrid bowl strongly mitigates the flame-to-flame interaction with respect to a conventional re-entrant bowl, leading to lower soot formation in the flame collision area. Moreover, faster flame propagation toward the cylinder axis is highlighted with a consequent higher soot oxidation rate in the late combustion phase.